ARE COMPANY SIZE, DEBT, PROFITABILITY AND MANAGERIAL OWNERSHIP INFLUENCE INCOME SMOOTHING? BEFORE AND AFTER THE COVID-19 PANDEMIC - Dewianawati, Dwi; Siswati, Endang; Pudjowati, Juliani; Lestari, Tri; Darmayanti, Novi (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
The purpose of conducting this research is to find out whether Company Size, Debt, Profitability, Managerial Ownership of Income Smoothing Practices before and after the Covid-19 pandemic were case studies on property and realestate companies on the Indonesia Stock Exchange in 2018-2022. With a total population of 13 companies, and a sample of 65 financial data studied within 5 years. The results of this study, researchers found that company size before the pandemic had no effect but after the pandemic company size had an effect on income smoothing before and after the Covid-19 pandemic. Meanwhile, Debt, Profitability, Managerial Ownership partially affect income smoothing before and after the Covid-19 pandemic.